Utilization Of Traditional Games As Educational Game Tools For Early Childhood - Elisabeth Nevi (PT. Padang Tekno Corp, 2026)
This study aims to examine the utilization of traditional games as educational play tools (EPT) in early childhood learning. The rapid development of technology has reduced children's interest in traditional games, making it necessary to preserve and utilize them as learning media. This research employs a descriptive qualitative approach with data collection techniques including interviews and observations. The results show that traditional games have significant potential in developing children's cognitive, motor, social-emotional, and character values. Furthermore, the integration of local wisdom into educational play tools can foster children's cultural awareness and identity from an early age. However, several challenges remain, such as limited references, teacher competence, and the influence of modern culture. Therefore, collaboration among various stakeholders is needed to optimally develop and implement local wisdom-based educational play tools